Reactive Transport Modelling of Chloride Ingress in Saturated Coral Aggregate Concrete - Guo, Bingbing; Li, Zhenming; Fu, Qiang; Wang, Yan; Huang, Daguan; Niu, Ditao (Frontiers in Materials, 2021)
Utilizing coral aggregate concrete (CAC) for construction on remote islands can significantly reduce construction cost and period, CO2 emission, and consumption of non-renewable energy. The durability of reinforced CAC structures is critically influenced by their resistance to chloride attack. In this study, a reactive transport modelling was developed to investigate chloride ingress in CAC, in which a COMSOL-PHREEQC interface based on MATLAB language was established. The experiment from the literature was taken as a benchmark example. The results show that the developed numerical model can accurately predict chloride transport in CAC. Differing from ordinary aggregate concrete (OAC), Kuzel’s salt does not appear in cement hydrate compounds of CAC during chloride ingress. The numerical results indicate that the penetration depth of chloride in CAC gradually increases as the exposure time is prolonged. When CAC is exposed to an external chloride solution, the decrease in the pH of the pore solution affects the precipitation of Friedel’s salt, which is detrimental to the chemical binding of chloride.